KONTRIBUSI PAJAK DAERAH DALAM MENINGKATKAN PENDAPATAN ASLI DAERAH (PAD) (Studi Kasus Badan Keuangan Daerah Kabupaten Karanganyar Tahun 2013-2017) - Tri Nurdyastuti; Anang Ma’ruf Arbiyanto (STIE AUB Surakarta, 2019)
This study aims to analyze the contribution and effectiveness of regional taxes in increasing the original income (PAD) of the Karanganyar district. The period used in this study is 5(five) years from 2013 to 2017. Data analysis techniques used in this study are contributions analysis, regional tax effectiveness analysis and descriptive statistical test and normality test. The sampling technique in this study used the census method so that all members of the population were used as samples and obtained a sample of 55. This research uses a quantitative approach. The results of the study revealed that the average contribution of regional taxes in increasing original income of the karanganyar district from 2013 to 2017 has fluctuated. The biggest contribution comes from street lighting tax with an average value of 19,10%. The level of effectiveness of local taxes in increasing regional income (PAD) of the Karanganyar district from 2013 to 2017 can be categorized as good. The highest effectiveness was achieved by restaurant tax in 2015 with a value of 297,64%. Keywords : : contribution, effectiveness, local tax, regional original income (PAD)